2020
DOI: 10.3390/ijerph17072277
|View full text |Cite
|
Sign up to set email alerts
|

Serum Uric Acid Level as a Harbinger of Type 2 Diabetes: A Prospective Observation in Taiwan

Abstract: Background: Current evidence suggests an association of uric acid with diabetes risk, but it is still unclear whether uric acid is merely a risk marker or an independent risk factor. We evaluate the impact of serum uric acid (SUA) levels on the future risk of developing type 2 diabetes, independent of other factors. Methods: A population-based cohort study was conducted among 4130 participants who were found to be free of type 2 diabetes at baseline recruitment in 2002. Baseline SUA measured in 2002 was longit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…In addition to causing gout, many studies have shown that hyperuricemia is also closely related to insulin resistance, and diabetes [27,28]. However, its function is a matter of debate [29].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to causing gout, many studies have shown that hyperuricemia is also closely related to insulin resistance, and diabetes [27,28]. However, its function is a matter of debate [29].…”
Section: Discussionmentioning
confidence: 99%
“…Viewed separately, a close relationship between SUA and IR has long been appreciated, which may be another mechanism to explain IR in obese people. Emerging evidence has shown that hyperuricemia is linked with IR and the subsequent promotion and development of T2DM ( 9 , 31 , 32 ). Similar to these studies, we found that the SUA level was higher in the high HOMA-IR group, and SUA was also an independent risk factor for HOMA-IR.…”
Section: Discussionmentioning
confidence: 99%
“…This hints that obese children oversecrete insulin in response to increasing insulin resistance to maintain the FBG in the normal range. However, this condition is strongly associated with alterations that represent an increased risk for the development of metabolic disorders and the occurrence of diabetes in adulthood ( 3 , 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperuricemia (HUA) is a major risk factor for several chronic conditions such as gout [1], cardiovascular diseases (CVDs) [2], diabetes [3], and hypertension [4]. HUA is also associated with increased hospitalization risks and healthcare expenditures [5].…”
Section: Introductionmentioning
confidence: 99%